A Critical Discussion on the Reasons and Impacts of International Decoupling - Florian W. Bartholomae; Chang-woon Nam (Intereconomics, 2023)
In the current economic policy debate, there are often calls to reverse advanced developments in globalisation and the international division of labour. Reasons such as greater business resilience, political independence and, from a climate perspective, less harmful production argue for not abolishing trade, but at least bundling a larger part of the value chain locally. However, such considerations are de facto made from the perspective of a highly developed and globally networked industrialised country. In contrast, this paper argues that trade activities can never be considered from the perspective of only one partner, but must always take into account the needs of all stakeholders, which in turn depend on the respective level of development.
Keywords: F13; F60; L14; 330; globalization; Globalisierung